Physical demands and physiological responses during elite field hockey - Lythe, J.; Kilding, A. E. (International Journal of Sports Medicine, 2011)
The aim of this study was to determine the physical demands of elite men's field hockey using modern time-motion analysis techniques. 18 elite male players (age: 24.4±4.5 yrs) participated in 5 matches, during which physical outputs of players were quantified using GPS units and heart rate monitors. The mean total distance covered by each individual player was 6 798±2 009 m. Mean total distance covered per position for 70 min (position70) was 8 160±428 m. Distance covered per position70 decreased by 4.8% between the 1st and 2nd halves (P<0.05). Fullbacks covered significantly less total distance than all other positions (P<0.05). High-intensity running (>19 km.h-1) comprised 6.1% (479±108 m) of the total distance covered and involved 34±12 sprints per player, with an average duration of 3.3 s. Average HR was higher in the 1st half (86.7% HRmax) than the 2nd half, (84.4% HRmax), though this was not significant (P=0.06). The results suggest that modern day elite field hockey is a physically demanding team sport. Quantification of the demands and outputs of players at this level provides a useful framework on which to develop conditioning practices. The difference in physical outputs observed for some positions suggests position-specific conditioning is required at the elite level.